The impact of paper industry corporation of the Philippines (PICOP) on the socio-economic condition of people in Mangagoy before and after downsizing - Cabaraban, Herbelle R.
The domination of industries has been the main scenario in the era of industrial revolution. In line with this, the study aims to determine the positive and negative impact of the introduction of an industry (PICOP) in the community of Mangagoy and to its people particularly on their socio-economic condition. The study shows that the first two decades of the paper industry had positive impact to the people of Mangagoy. The industry provided employment for almost 70% of the workforce of the community. However due to the Asian crisis in 1990, the company was also affected that led to downsizing. The company needed to lay off workers and this was the beginning of the difficulties experienced by the people of Mangagoy. The downsizing of the paper industry resulted to the increase of unemployed people in the community. As many people lost their jobs, socio- economic conditions of the people negatively change. The ability of the people to buy their basic needs declined. Furthermore, health and education are also adversely affected in conclusion, birth and decline of industries in a community may provide positive and negative impacts on the community.